Various morphologic features of Gnathostoma spinigerum in histologic sections: Report of 3 cases with reference to topographic study of the reference worm - Vorachai Sirikulchayanonta (2018)
Gnathostomiasis is common in Southeast Asian countries and can be found sporadically in other parts of the world mainly due to human migration. The definitive diagnosis can be given either by identification of the parasite isolated from the patient or through histologic section of the lesion. It is therefore important for pathologists to be familiar with the morphology of parasitic larvae which varies according to the levels of section-cutting so that the diagnosis will not be misled. We present three cases of gnathostomiasis with different features of parasitic morphology and compare these with the reference adult worm.